Application of the simplex-centroid design with process variable in the optimization of production conditions of B100 biodiesel from sunflower oil - Dias, Gabriel Henrique; Guedes, Carmen Luisa Barbosa; da Silva, Elisangela Tavares; Angilelli, Karina Gomes; Coppo, Rodolfo Lopes; Borsato, Dionisio (Acta Scientiarum. Technology, 2014)
A simplex-centroid design was applied to optimize conditions for obtaining B100 biodiesel from sunflower oil using different catalysts with methanol and ethanol as process variable. Sodium methoxide was indicated as the best catalyst in the transesterification reaction with methanol at a 98.30% yield. Reaction yield was optimized only to 89.65% when ethanol as process variable and KOH as catalyst were employed. Tests with the obtained products, in optimal conditions, indicated that they were within the parameters established by Brazilian legislation and by the European Union. Â 